Integration of mathematics learning strategies with the cultivation of Islamic teaching values in the context of applicable jurisprudence - Agus Miftakus Surur; Magfirah Perkasa; Sugiarni Sugiarni (Universitas Negeri Malang, 2023)
This article aims to describe the application of several mathematical sciences in the study ofjurisprudence which are included in mathematics learning strategies. This is based on the problemsseen in classroom learning that the delivery of mathematics is only the delivery of theory orformulas. Even though it is sometimes linked to everyday contexts, it is still lacking in linking it toreligion, especially to the science of jurisprudence which is included in the field of Islamic science.Some of the fiqh studies presented here are considered to be often related to everyday life. In detail,you can use a similar analogy. The method used is literature study research, which is sourced fromrelated documents that are in accordance with the study. The results of this paper show thatmathematics is indeed used in fiqh, so it can be used in mathematics learning strategies. Stages thatcan be included are mention of Allah's name, use of terms, visual illustrations, examples, insertionof verses/hadith, history, and topic networks. The study of jurisprudence that is connected tomathematics is the problem of Thaharah, prayer, Zakat, Fasting, Hajj and Faraid. All of these studiesuse basic knowledge in mathematics which is easy to apply.